In silico analysis and structure modelling of gahp2, a conserved hypothetical protein related to thermal stress response in Glaciozyma antarctica PI12 - Makdi Masnoddin; Clemente Michael Wong Vui Ling; Nur Athirah Yusof (Universiti Malaysia Sabah, 2025)
The genomic data of the native Antarctic yeast, Glaciozyma antarctica PI12, has garnered attention due to its distinctive thermal adaptation. Nonetheless, a significant percentage of the proteins associated with thermal stress adaptation were identified as conserved hypothetical proteins (HPs), suggesting that these proteins remain experimentally uncharacterized. Consequently, this study aims to determine the structural characteristics of GaHP2, an uncharacterized conserved hypothetical protein believed to play a significant role in the thermal stress response. The gene was subjected to an extensive analysis utilizing computational tools to explore its function, physicochemical properties, and three-dimensional structure. Functional annotation was executed using NCBI BLAST and InterPro Scan; physicochemical properties were evaluated with ExPASy's ProtParam; homology modeling was performed using Phyre2 and AlphaFold2, while structure validation, refinement, and superimposition were implemented with MoD Refiner and UCSF Chimera. The results indicated that the homology modeling approach effectively generated reliable 3D models of GaHP2. The high confidence score (PROCHECK), stereochemical quality (VERIFY3D), energy of the protein chain (ANOLEA), and RMSD of 0.540 Å indicate that the proposed model closely reflects the actual protein conformation. One interesting finding of the study was the correlation between the presence of aromatic clusters in GaHP2 and its stability at higher temperatures, a finding not previously documented in cold-adapted Antarctic proteins. The GaHP2 protein was also found to contain domains that encoded oxygen-binding and/or oxygen- transporting goblins, as indicated by functional analysis, suggesting a role in cold adaptation under low oxygen conditions. This research illustrates that thermal stress proteins may possess distinctive structural flexibility and stability that enable them to function under thermal stress, thereby safeguarding host organisms from heat aggregation and cold denaturation.